2009
DOI: 10.1002/er.1494
|View full text |Cite
|
Sign up to set email alerts
|

A comparison study of energy and exergy performance of a hybrid photovoltaic double-pass and single-pass air collector

Abstract: SUMMARYIn this present paper, analysis based on energy and exergy of double-pass hybrid photovoltaic thermal (HPV/T) air collector having air flow in the opposite direction in ducts has been carried out based on initial cost, annual savings and return on investment. Choice of the location is made to cover different climatic conditions prevailing in India e.g. hot and dry climate represented by Jodhpur, warm and humid climate represented by Mumbai, moderate climate represented by Bangalore, cold and cloudy clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Tiwari et al [111] evaluated the overall efficiency performance of an unglazed PVT air collector for Indian climatic condition and results gave the optimal air flow rate, length and depth of duct. Raman and Tiwari [114,115] have studied the annual thermal and exergy efficiency of PVT air collector for five different climatic conditions of India. It was observed that the exergy efficiency is 40-50% lower than the thermal efficiency under strong solar radiation.…”
Section: Exergy Efficiencymentioning
confidence: 99%
“…Tiwari et al [111] evaluated the overall efficiency performance of an unglazed PVT air collector for Indian climatic condition and results gave the optimal air flow rate, length and depth of duct. Raman and Tiwari [114,115] have studied the annual thermal and exergy efficiency of PVT air collector for five different climatic conditions of India. It was observed that the exergy efficiency is 40-50% lower than the thermal efficiency under strong solar radiation.…”
Section: Exergy Efficiencymentioning
confidence: 99%
“…More details of governing equations derivation are found in References [8,[11][12][13]15,16,18]. Figure 1 shows the equivalent thermal resistant circuit of a PV/T air collector [18].…”
Section: Thermal Analysismentioning
confidence: 99%
“…The electrical efficiency of a PV module can be defined as the ratio of actual electrical output power to input the rate of solar energy incident on the PV surface as follows [7,8,[11][12][13][14][15][16][17][18]:…”
Section: Electrical Analysismentioning
confidence: 99%
See 2 more Smart Citations